Analysis of Facility Needs, Policies, Leadership Support, and Work-Life Balance on Female Worker Performance at Pertamina IHC Clinic - Hamsinah, Hamsinah; Sunarsi, Denok; Nuraeni, Eni (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This study aims to analyze the needs of facilities, policies, leadership support, and work-life balance on the performance of female workers at the Pertamina IHC Clinic. This study uses qualitative and quantitative methods (Mix Method) using data analysis using SEM_PLS version 3.0. Data were collected through a survey involving 384 female workers at the Pertamina IHC Clinic, the sampling technique using simple random sampling. The results of the study indicate that facilities and policies have positive and significant implications for the performance of female workers. However, leadership support does not have a significant direct impact. Through the mediation of work-life balance, policies and leadership support are proven to significantly improve performance, while facilities do not show a significant effect. Facilities such as lactation rooms, break rooms, and access to training are considered supportive, as are special leave policies, gender equality, and protection from harassment. Leadership support that includes work flexibility, career development, and appreciation is also an important factor. The main challenges faced include the limited implementation of facilities and policies evenly, as well as the low representation of women in leadership. Therefore, an evaluation of facilities, gender-based leadership training, and a fair policy monitoring system are needed to improve the performance of female workers sustainably.